A new species of the hippolytid shrimp genus Thor Kingsley, 1878 (Crustacea: Decapoda: Caridea) from Hainan Island, China - Xu, Peng; Li, Xinzheng (Zootaxa, 2014)
A new species of the caridean family Hippolytidae, Thor hainanensis sp. nov., is described and illustrated based on specimens from Hainan Island, China. The carpus of the second pereopod is six-segmented; the mandible has only the incisor process and the molar process; the third segment of antennular peduncle has one subtriangular dorsal scale. Those morphological characters easily classify this species into the genus Thor Kingsley, 1878. First pereopod with epipod distinguishes the present new species from the other members of the genus, because the existence of epipod among different pereopods is considered to be fixed at interspecific level and all the described species of this genus lack the epipod on the first pereopod.